PENINGKATAN HASIL BELAJAR SOAL CERITA LUAS JAJARGENJANG DAN SEGITIGA DENGAN LANGKAH POLYA DI SD - Syalmani, Syalmani (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The results in SDN 09 Air Pacah, learning about the story and the vast parallelogram triangle using lecture. The aim is to describe the learning steps Polya. Kind is the PTK. The subject of students and teachers. Data use test. The results for the RPP cycle I and II, 84 and 89. Teacher activity cycles I and II 85. and 91. Student activity cycles I and II 81 and 87. Learning outcomes cycles I and II 75 dan 82. Research can improve student learning outcomes. Kata Kunci: hasil belajar; soal cerita luas jajargenjang dan segitiga; langkah polya